Prospects for Food Fermentation in South-East Asia, Topics From the Tropical Fermentation and Biotechnology Network at the End of the AsiFood Erasmus+Project - Waché, Yves; Do, Thuy-Le; Do, Thi-Bao-Hoa; Do, Thi-Yen; Haure, Maxime; Ho, Phu-Ha; Kumar Anal, Anil; Le, Van-Viet-Man; Li, Wen-Jun; Licandro, Hélène; Lorn, Da; Ly-Chatain, Mai-Huong; et al. (Frontiers in Microbiology, 2018)
Fermentation has been used for centuries to produce food in South-East Asia and some foods of this region are famous in the whole World. However, in the twentyfirst century, issues like food safety and quality must be addressed in a World changing from local business to globalisation. In Western Countries, the answer to these questions has been made through hygienisation, generalisation of the use of starters, specialisation of agriculture and use of long-distance transportation. This may have resulted to a loss in the taste and typicity of the products, to an extensive use of antibiotics and other chemicals and eventually, to a loss in the confidence of consumers to the products. The challenges awaiting fermentation in South-East Asia are thus to improve safety and quality in a sustainable system producing tasty and typical fermented products and valorising by-products. At the end of the AsiFood Erasmus project, the goal of this paper is to present and discuss these challenges as addressed by the Tropical Fermentation Network, a group of researchers from universities, research centres and companies in Asia and Europa. This paper presents actions on quality of traditional fermented food and screening of functional bacteria and starters, food safety strategies and research for new antimicrobial compounds and development of more sustainable fermentations and valorisation of by-products. One specificity of this network is also the multidisciplinary approach dealing with microbiology, food, chemical, sensorial and genetic analyses, biotechnology, food supply chain, consumers, ethnology.